Physiochemical Characteristic and Antioxidant of Solid Bath Soap Containing Gerga Orange (Citrus nobilis L. var RGL) Peel: The Formula and Anti-oxidant Properties of The Gerga Orange Peel (Citrus nobilis L. var RGL) Extract-containing Organic Soap - Noviarni, Intan; Ningsih, Syukrya (Al-Kimia, 2024)
The study primarily focused on analyzing the prospective utilization of waste biomass, particularly those possessing antioxidant properties, for soap formulation. Antioxidants serve as radical scavengers, protecting against oxidative damage in both soap and human skin. This research aims to assess solid bath soap’s efficacy and antioxidant potential when combined with Gerga orange peel (Citrus nobilis L. var RGL) extract. The quality of the bath soap was evaluated based on the Indonesian National Standard (INS) 3532:2021. The antioxidant activity of the soap was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging technique. The solid bath soap formulations underwent rigorous quality testing, and the findings indicated that they exceeded the standards set by INS 3532:2021 for solid bath soap quality. These formulations demonstrated superior performance in various parameters, including pH levels, moisture content, free fatty acids, free alkali, solubility in alcohol, and foaming capabilities. The antioxidant activity of each soap formulation was quantified by its IC50 value. The results showed that the level of antioxidant activity in the solid bath soap increased proportionally with the quantity of Gerga orange peel extract used. Overall, the findings suggest a favorable potential for utilizing Gerga orange peel extract as a cost-effective and feasible natural antioxidant component in soap production.